Marketing Management Transformation: YouTube Video Analysis Approach Supporting MSMEs with Disabilities in Indonesia - Ilham, Moh.; Sudarmiatin, Sudarmiatin (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research presents a qualitative research method with an analytical approach to several videos on YouTube related to Marketing Management support for MSMEs for Persons with Disabilities in Indonesia. The research implementation method involves selecting relevant YouTube videos, content analysis, and preparing strategy recommendations. Also with the technique of selecting the 10 highest viewed videos after being filtered by 3 search hashtags, namely #Marketing #MSMEs #Disability. The results of this research reveal that there is still a small intensity in the number of viewers whose highest views are still below 1000, there is still a need for special assistance for MSMEs with disabilities, whether families or other parties, there is still a need for effective marketing strategies, and strengthening branding through social media, one of which is YouTube. The implications of this research are improving marketing strategies, strengthening supporting communities, visibility and accessibility of Disabled MSMEs, as well as increasing public acceptance of their products and services for Disabled MSMEs in Indonesia.